2005
DOI: 10.1177/0047287505278979
|View full text |Cite
|
Sign up to set email alerts
|

Preference and Positioning Analyses of Overseas Destinations by Mainland Chinese Outbound Pleasure Tourists

Abstract: The objective of this study is to explore the competitiveness of overseas destination countries where potential Mainland Chinese outbound tourists consider making an overseas travel and the positioning of these destination countries. According to the analysis of importance of a destination’s attributes, Mainland Chinese respondents considered “safety” and “beautiful scenery” to be the most important attributes. On the basis of KYST (Kruskal, Young, Shepard, and Torgerson) analysis, Mainland Chinese respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 26 publications
1
105
0
3
Order By: Relevance
“…Agrusa, Kim & Wang, 2011;Kim et al, 2005;Ryan & Mo, 2002;Sparks & Pan, 2009). This study provides further managerial implications for tourism marketers and product developers.…”
Section: Managerial Implicationsmentioning
confidence: 79%
See 3 more Smart Citations
“…Agrusa, Kim & Wang, 2011;Kim et al, 2005;Ryan & Mo, 2002;Sparks & Pan, 2009). This study provides further managerial implications for tourism marketers and product developers.…”
Section: Managerial Implicationsmentioning
confidence: 79%
“…For instance, Ryan and Mo (2002) researched the decision-making processes of Chinese tourists visiting New Zealand and found that the main motivation was to see new places. Kim and Guo (2005) found that mainland Chinese respondents considered 'safety' and 'beautiful scenery' to be the most important attributes, whereas 'level of economic development' and 'good place for shopping' were regarded as the least important. The perceived importance of 'safety' amongst Chinese outbound tourists was also reported by Sparks and Pan (2009) and Li et al (2015).…”
Section: Chinese Long-haul Outbound Touristsmentioning
confidence: 97%
See 2 more Smart Citations
“…To capture Chinese travellers' perceptions, 21 image attributes measured the tourism product generally offered to Chinese travellers such as attractive scenery and natural attractions and cultural/historical attractions, and the more general images of Western Europe such as cities with modern technology, quality accommodation, and quality tourist services [60,63,65,66,73]. The items were measured on a bipolar 7-point Likert scale anchored on [1] Offers very little and [7] Offers very much.…”
Section: Survey Instrumentmentioning
confidence: 99%